the degree of practice of the deans and heads of departments at the University of M'sila for participatory leadership in light of the application of the university enterprise project. - Azoug, Djamila (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The current study aimed to reveal the degree of practice of the deans and heads of departments at the University of Mohamed Boudiaf in M'sila for participatory leadership in light of the application of the university enterprise project. In order to achieve this objective, we used the descriptive analytical approach by applying a participatory leadership questionnaire of its owner (Hussam Jihad Farajallah), which consisted of four axes: decision-making process, administrative development, delegation and crisis management, this questionnaire contains (34) phrases, and it was distributed on a sample consisted of (30) members of the deans and heads of departments at the University of M'sila by (58.82%) of the research community. After statistical analysis, the study reached the following results: The practice of participatory leadership by the deans and heads of departments at the University of M'sila, in light of the application of the university institution's project, was highly at the level of all the axes of the questionnaire. There are no statistically significant differences in the degree of practicing participatory leadership according to the job title variable (Dean/Department Head) in light of the application of the university enterprise project, either in the three fields of study (decision-making, administrative development, crisis management) or in the questionnaire as a whole, while the difference was statistically significant in the field of delegation and in favor of the heads of departments. There are no statistically significant differences in the degree of practicing participatory leadership by the deans and department heads in light of the application of the university enterprise project in either the fields of study or the questionnaire as a whole, according to the variables of academic rank and number of years of service at the university.